(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article discusses the use of metaphors in phraseological units. It analyzes the semantic and stylistic aspects of phraseological units, their role in speech, and their use as a descriptive tool. The article reflects on how metaphors reveal the uniqueness of national culture and language, and how they enrich the communicative process